pribaikalye and zabaikalye - Grigoryeva, Elena (project baikal, 2019)
…Whether God’s retribution was spilt onto us… Vladimir Vysotsky, Hunting from Helicopters © Akbar Muhammad. Translation, 2016 Siberia and the Far East are the main source of Russian wealth. It is small towns that bear the brunt of natural disasters, fires and floods. In Tulun, the dam failed under the pressure of the small river Iya; the flood returned a month later, and hundreds of households were submerged in water again. The Uda River submerged Nizhneudinsk. While Ust-Ilimsk was suffocated in smoke, the disaster was spreading globally. The soot clouds produced by Siberian fires have already reached California. Both fire and water are recompense for the environmental disorder and the wanton destruction of the taiga. The article by Andrey Bolshakov speaks about disasters and landscape-oriented design; Nikolai Kradin presents the history of small towns in Zabaikalye, and young Siberian urbanists propose their projects for regeneration of the urban environment in Nerchinsk and Sayansk.